Successful Imatinib Treatment for Systemic Mastocytosis Associated With Myelodysplastic/Myeloproliferative Neoplasm: Report of a Case and Literature Review - Barozzi, Enrico; Bucelli, Cristina; Grifoni, Federica Irene; Gianelli, Umberto; Iurlo, Alessandra; Cattaneo, Daniele (Frontiers in Oncology, 2022)
Systemic mastocytosis (SM) is a heterogeneous disease characterized by the expansion of mast cells in one or more tissues, frequently characterized by the presence of KITD816V mutation. The updated World Health Organization (WHO) classification of myeloid neoplasms recognizes SM with an associated hematological neoplasm (SM-AHN) as a new subtype among the others, which is depicted by the coexistence of SM with another hematological clonal disease. Prognosis is very different among SM patients, while its treatment, although highly personalized, is still challenging. Here we report a case of KITD816V-unmutated SM associated with MDS/MPN successfully treated with imatinib.